2021
DOI: 10.1088/1755-1315/948/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and characteristics of the Makassar tarsius Tarsius fuscus fischer, 1804 sleeping nest in the tropical primary and secondary forests of South Sulawesi

Abstract: Tarsius fuscus, whose distribution is limited to the southern part of South Sulawesi, Indonesia, is threatened by poaching and habitat loss, with the latter leading to the disappearance of its sleeping nest locations, despite the species’ wide range of habitat requirements. This study aimed to identify the distribution and characteristics of T. fuscus sleeping nests. Research took place in Bantimurung Bulusaraung National Park primary and secondary forest areas and Hasanuddin University Educational Forest. Sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The chi-square test confirmed that the calculated χ2 28.727 was higher than the χ2 table (0.05, k-1), indicating that tarsier preferred some specific nest trees. Tarsiers generally preferred Ficus trees as nests (Andriyani et al 2021;Gursky 2002), and this was further confirmed through the research in Button Island by Mansyur et al (2016), where 21 of 32 sleeping areas found for the primates were Ficus species. Gursky (2002) reported similar results that 90% of the sleeping trees used by the Tarsius spectrum in Tangkoko Nature Reserve were large beringin trees.…”
Section: Nest Tree Preferencesmentioning
confidence: 65%
See 1 more Smart Citation
“…The chi-square test confirmed that the calculated χ2 28.727 was higher than the χ2 table (0.05, k-1), indicating that tarsier preferred some specific nest trees. Tarsiers generally preferred Ficus trees as nests (Andriyani et al 2021;Gursky 2002), and this was further confirmed through the research in Button Island by Mansyur et al (2016), where 21 of 32 sleeping areas found for the primates were Ficus species. Gursky (2002) reported similar results that 90% of the sleeping trees used by the Tarsius spectrum in Tangkoko Nature Reserve were large beringin trees.…”
Section: Nest Tree Preferencesmentioning
confidence: 65%
“…The selection of such specific sleeping areas indicated that tarsiers had a preference for trees with certain characteristics, such as low light intensity, availability of surfaces to grip while sleeping, shelter from rain and wind, and multiple entrances or exits to avoid predators (MacKinnon and MacKinnon 1980). This also showed that although tarsiers were often found in secondary and disturbed forests (Krisnatalya et al 2020;Andriyani et al 2021;Sapsuha et al 2021;Zakaria et al 2022), this species preferred forests with dense vegetation cover (Bienkowski et al 2018; Rizki and Abiduna 2020; Shekelle 2020). The information on nest characteristics, preferences, and factors influencing nest tree selection provided a better understanding of the specieshabitat relationships.…”
Section: Nest Tree Preferencesmentioning
confidence: 99%
“…Although the IVI value of F. virens was the highest, this plant's density and relative frequency were relatively low. Most of the researchers (Mustari et al 2013;Saroyo et al 2014;Gursky 2016;Arrijani and Rizki 2019;Andriyani et al 2021) found that Ficus is a tree species that is widely used as nest trees in secondary forests. Furthermore, Gursky (2016) stated that F. caulocarpa is the most commonly used tree for T. spectrumgursykae nest, with 30-700 cm circumference.…”
Section: Discussionmentioning
confidence: 99%